Desempenho operacional e propriedades físico-mecânicas de um Latossolo em função do tipo de pneu e cargas aplicadas à barra de tração - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
The changes of soil physical-mechanical properties, arising from the traffic of machines in farming operations, have been widely studied, emphasizing the negative effects of soil compaction on crop productivity. This work aimed to evaluate the operational performance and physical-mechanical properties of an Oxisol as function on the type of tire and loads applied to the traction bar. Before the tests had been carried out in the experimental area was built the correction curve of the soil penetration resistance (PR) versus soil water content, the soil water retention curve (WR) and the modeling of load support capacity of the soil (LSC). In conducting the experiment was adopted the design in random blocks of plots subdivided, in factorial designs 2x5, where the plots were made up of two types of tire structure: radial and bias, and the subplots were five average loads imposed on the traction bar of the tractor by a braking tractor (0; 4.32; 9.80; 12.48 and 16.69 kN) with four repetitions per treatment in a total of 40 experimental units. To evaluate the influence of the kind of tires in the physical-mechanical characteristics of the soil was evaluated in depth of 0-0.05 m soil density, degree of compaction, WR and preconsolidation pressure, and at the depth of 0-0.15 m was assessed the PR. The operational performance in the set (loads-tire) was assessed by the average power in traction bar, wheel slip, consumptions per hour and specific of fuel. The results of the physical-mechanical analysis demonstrated that both tires and forces applied to the traction bar not caused additional compactation to the soil. There was an average increase of 4% and 3.7% in soil density and degree of compression, respectively, for both tires and loads applied to the traction compared to the values before the test with tractor traffic. The WR did not change when the tractor tested used the radial tire on all loads, about the bias tire in the load 0 kN there was a reduction no significant of macropores and micropores, and higher loadings did not cause changes in it. The PR values remained below the value found in the humidity of the field capacity, that is, there was no change in the same for both tires and loads applied to the traction bar. The results of the preconsolidation pressure for all treatments remained on "region b" of the LSC, characterized by not providing additional compression to the soil. The bias tire provided greater average power in traction bar when compared to radial tire, however, the wheel slip, consumptions per hour and specific of fuel were higher for the radial tire than the bias tire. It can be concluded that both tires and loads applied to the traction bar not caused additional compression to the soil; the bias tire presented better operational performance compared to radial tire.
Keywords: Compactação do solo; Modelagem analítica; Preconsolidação; Consumo de combustível; Soil compaction; Analytical modeling; Preconsolidation; fuel consumption; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA; ENGENHARIA AGRICOLA::MAQUINAS E IMPLEMENTOS AGRICOLAS